MASALAH-MASALAH PEMBELAJARAN TEMATIK DI SEKOLAH DASAR (Studi Kasus di SDN 200210 Kota Padangsidimpuan) - Murni Ati; Padli Tumanggor; Ramanida Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Thematic learning is an integrated learning approach that combines various subjects into a single theme in order to make learning more meaningful. However, in its implementation, problems are still encountered that can hinder the effectiveness of learning. The purpose of this research article is to identify the problems that arise in the implementation of thematic learning in elementary schools. This study employs a descriptive qualitative approach using a case study method. The data in this study were collected through interviews with classroom teachers and documentation. The results indicate that classroom teachers experience difficulties in the planning of thematic learning, the implementation of thematic learning, and the assessment of thematic learning. Possible solutions include improving teachers’ competencies through continuous training, utilizing interactive media, and collaborating with fellow teachers in lesson planning